The relationship between anesthesia and melatonin: a review - Guo, Rui; Ye, Junming; Liao, Baozhen; Luo, Xin; Rao, Panguo (Frontiers in Pharmacology, 2023)
This comprehensive review delves into the intricate relationship between anesthesia and melatonin. Melatonin, a vital endogenous hormone produced by the pineal gland, plays a pivotal role in regulating circadian rhythms. However, anesthesia and surgery can disrupt melatonin secretion, resulting in sleep disturbances and postoperative neurocognitive dysfunction. This review explores the potential benefits of perioperative melatonin administration, including its ability to alleviate anxiety, relieve pain, improve perioperative sleep, and exhibit immunomodulatory and anti-tumor effects, making it especially advantageous for cancer surgery patients.